Nurse teacher candidates learned to use social media during the international teacher training course - Salminen, Leena; Gustafsson, Marja-Liisa; Vilén, Liisa; Fuster, Pilar; Istomina, Natalja; Papastavrou, Evridiki (My University, 2016)
Abstract The purpose of this study was to describe the nurse teacher candidates' learning outcomes and experiences in social media during the international nurse teacher training course, Empowering learning environments in nursing education, Intensive Program (EleneIP). The pre-post research design was used. The data was collected before and after the course, with the questionnaire consisting of structured and open questions. Altogether, 24 nurse teacher candidates from four different European countries participated in the course and this study. The results showed that the knowledge of using social media applications increased during the course from 5.2 (range 1-9) to 8.1 (range 4-10), and their skills increased from 4.5 (range 1-8) to 7.6 (range 4-10).The main topics learnt during the course were divided in two categories: subjects of the course and teaching and learning methods. The students' experiences concerning the EleneIP course were positive in both categories. The international group created during EleneIP course also allowed the students to achieve another important aim, learning from a collaborative group the importance and possibilities of different learning environments, considering the cultural and social characteristics of each country participating in it.
Keywords: Nurse teacher; Nurse teacher candidate; Social media; Nursing education